Exports as a Determinant of Inflation in Kenya: Disaggregated Econommetric Analysis - Kiganda, Evans Ovamba; Adhiambo, Scholastica; Obange, Nelson (European Scientific Journal, ESJ, 2017)
The purpose of this study was to examine exports as a determinant of inflation in Kenya: A disaggregated econometric analysis with specific objectives of establishing the relationship between domestic exports and inflation in Kenya and determining the relationship between re - exports and inflation in Kenya. This was occasioned by inconclusive and incomprehensive analysis on the relationship between exports and inflation given mixed results and failure by scholars to disaggregate total exports into domestic exports and re-exports. Correlation research design was employed using monthly time series obtained from Central Bank of Kenya (CBK) data spanning 132 months from January 2005 to December 2015.Vector Autoregressive (VAR) techniques of cointegration, Granger causality and impulse response analysis were employed. Results indicated a significant positive and negative long run relationship between domestic exports and re- exports with inflation in Kenya respectively that were supported by the impulse response analysis. A unidirectional causality running from domestic exports to inflation and re-exports to inflation was also established. The study concluded that domestic exports and re-exports determine inflation in Kenya with domestic exports having greater influence and therefore recommended that the government of Kenya needs to advocate for a trade policy that aims at reducing exports of domestically produced products and increase re-exports. This will ensure that only surplus is exported to reduce shortage of domestically produced commodities hence a reduction in price for the products.